KASIHANILAH AKU YA TUHAN: KRITIK NARATIF MENGENAI KASIH IBU MENURUT MATIUS 15:21-28 - Raulina, Raulina; Tambun, Roy Haries Ifraldo (Phronesis: Jurnal Teologi dan Misi, 2024)
The role of a mother is very important in shaping the character and personality of children. The narrative in Matthew 15:21-28 depicts the dedication of a Canaanite mother who humbles herself for the healing of her daughter. This story serves as a powerful representation of the essence of motherhood and an antithesis to the increasingly common phenomenon of being motherless in today's society. This research aims to explore the contribution of the Canaanite woman's narrative in understanding issues related to motherhood and the condition of being motherless. The methodology used is qualitative, with an in-depth analysis of the biblical text and its relevance to family complexities. The results indicate that this story offers a model of motherhood that emphasizes total dedication, humility, and persistence in seeking help. These values can be implemented through community support, parenting education programs that integrate spiritual values, and psychological support for mothers facing challenges in fulfilling their maternal roles. Furthermore, this narrative teaches that true motherhood has a strong spiritual dimension, reflecting responsibilities that go beyond the physical and emotional needs of children. Thus, this story not only functions as a historical narrative but also provides a comprehensive paradigm of motherhood that can address the crisis of being motherless in contemporary society.